Dunkin' the donut: a study on students' patterns of language use through technology applications in independent language learning / Norizul Azida Darus and Norhajawati Abdul Halim - Darus, Norizul Azida; Abdul Halim, Norhajawati (Universiti Teknologi MARA, Perlis, 2020)
Any language can be acquired at any time, but to acquire the language, one needs to learn the language. Learning a second or foreign language is not a favourite among second or foreign language learners. This is because learning a language is a very intense time-consuming activity. Learning is often unsuccessful because learners receive impoverished or insufficient input and lack of motivation. To this, second language or foreign language teachers play the most significant role to help and motivate the students to acquire the said language. The preferred method is to be immersed into the actual ecosystem of the target language and become part of the language ecosystem. The other way is to dunk the learners into the artificial ecosystem of the language classroom. In dunking, the learners are immersed temporarily and repeatedly into the simulated ecosystem language. As can be seen now, technology remains the only viable option to get enough interactive contact with the target language. Using interesting software is one of the methods in making learning more interesting. Furthermore, the students are able to practice the language not only during class time, but on their own free time outside of class hours, that is during students' independent time of learning. The findings revealed that most students found using the applications has improved their language learning. The role of teachers on the other hand is to provide instructions and assist whenever necessary and needed by the students.